Hubungan Antara Dukungan Sosial Rekan Kerja Dan Komitmen Karier Pada Guru SMA di Kota Salatiga - Ariani, Dwi Setya (Faculty of Psychology, Diponegoro University, 2015)
The purpose of this research is to verify the correlation between Coworker Support and Career Commitment on Teachers in Private High Schools of Department of Education, Youth and Sport. There are two scales used in this research, i.e. Coworker Support Scale and Career Commitment Scale. The participants of this research are 60 teachers of private high schools in Salatiga, Indonesia. Data analysis used in this research is Pearson Product Moment Correlation. The result of data analysis showed that there was a significant correlation between Coworker Support and Career Commitment on Teachers in Private High Schools of Department of Education, Youth and Sport of Salatiga (r = .541; p < .05).